Multifactorial Origin of Exertional Rhabdomyolysis, Recurrent Hematuria, and Episodic Pain in a Service Member with Sickle Cell Trait - Nyamkhishig Sambuughin; Mingqiang Ren; John F. Capacchione; Ognoon Mungunsukh; Kevin Chuang; Iren Horkayne-Szakaly; Francis G. O’Connor; Patricia A. Deuster (Case Reports in Genetics)
Individuals with Sickle Cell Trait (SCT), generally considered a benign carrier state of hemoglobin S (HbAS), are thought to be at risk for exertional rhabdomyolysis and hematuria, conditions that can also be caused by various other acquired and inherited factors. We report an SCT positive service member with an exertional rhabdomyolysis event, recurrent hematuria with transient proteinuria, and episodic burning pain in the lower extremities. Clinical and genetic studies revealed the multifactorial nature of his complex phenotype. The service member was taking prescription medications known to be associated with exertional rhabdomyolysis. He carried a pathogenic mutation, NPHS2 p.V260E, reported in nephropathy and a new variant p.R838Q in SCN11A, a gene involved in familial episodic pain syndrome. Results suggest that drug-to-drug interactions coupled with the stress of exercise, coinheritance of HbAS and NPHS2 p.V260E, and p. R838Q in SCN11A contributed to exertional rhabdomyolysis, recurrent hematuria with proteinuria, and episodic pain, respectively. This case underscores the importance of comprehensive clinical and genetic evaluations to identify underlying causes of health complications reported in SCT individuals.